ANALISIS TINGKAT KESULITAN KEUANGAN TERHADAP TINGKAT HUTANG DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Sub Sektor Pertambangan Yang Terdaftar Di BEI) - Sirrul Hayati; Tati Atmayanti (Universitas Islam Negeri Mataram, 2022)
This study aims to analyze the relationship between the level of Financial Distress and the Level of Debt with the Independent Board of Commissioners as an Intervening Variable. The type of research used in this research is quantitative and then processed with statistical methods. The population in this study are all companies in the mining sector which are listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study was purposive sampling. Data analysis techniques using descriptive statistics, classic assumption test, multiple regression, hypothesis testing. Based on the results of data processing and data analysis in this study, it was found that financial distress had a positive and significant effect on debt levels, financial difficulties had a positive and significant effect on independent commissioners, independent commissioners had no significant effect on debt levels, independent commissioners were unable intervene the effect of financial difficulties on debt levels. In this study, financial difficulties and an independent board of commissioners have a joint effect of around 62.3% on debt levels. This study aims to analyze the relationship between the level of Financial Distress and the Level of Debt with the Independent Board of Commissioners as an Intervening Variable. The type of research used in this research is quantitative and then processed with statistical methods. The population in this study are all companies in the mining sector which are listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study was purposive sampling. Data analysis techniques using descriptive statistics, classic assumption test, multiple regression, hypothesis testing. Based on the results of data processing and data analysis in this study, it was found that financial distress had a positive and significant effect on debt levels, financial difficulties had a positive and significant effect on independent commissioners, independent commissioners had no significant effect on debt levels, independent commissioners were unable intervene the effect of financial difficulties on debt levels. In this study, financial difficulties and an independent board of commissioners have a joint effect of around 62.3% on debt levels.